Skillful regional prediction of Arctic sea ice on seasonal timescales. Issue 10 (21st May 2017) - Bushuk, Mitchell; Msadek, Rym; Winton, Michael; Vecchi, Gabriel A.; Gudgel, Rich; Rosati, Anthony; Yang, Xiaosong
Abstract: Recent Arctic sea ice seasonal prediction efforts and forecast skill assessments have primarily focused on pan‐Arctic sea ice extent (SIE). In this work, we move toward stakeholder‐relevant spatial scales, investigating the regional forecast skill of Arctic sea ice in a Geophysical Fluid Dynamics Laboratory (GFDL) seasonal prediction system. Using a suite of retrospective initialized forecasts spanning 1981–2015 made with a coupled atmosphere‐ocean‐sea ice‐land model, we show that predictions of detrended regional SIE are skillful at lead times up to 11 months. Regional prediction skill is highly region and target month dependent and generically exceeds the skill of an anomaly persistence forecast. We show for the first time that initializing the ocean subsurface in a seasonal prediction system can yield significant regional skill for winter SIE. Similarly, as suggested by previous work, we find that sea ice thickness initial conditions provide a crucial source of skill for regional summer SIE. Key Points: Coupled dynamical prediction system skillfully predicts regional sea ice extent on seasonal timescales Ocean subsurface temperature initialization yields North Atlantic regional winter skill at lead times of 5‐11 months Sea ice thickness initialization provides a key source of summer regional skill at lead times of 1‐4 months